2019
DOI: 10.1177/0020764019852654
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the schizophrenia suicide attempts in comparison with the suicide attempts with other diagnosed psychiatric disorders: An Egyptian study

Abstract: Background: There has been much literature on schizophrenia, but little is known about the characteristic features of suicide attempts with schizophrenia in comparison with the suicide attempts with other diagnosed psychiatric disorders. Aims: The objective of this study was to clarify the specific characteristics and risk factors among suicide attempters with schizophrenia that differentiate them from other psychiatric disorders. Methods: Thirty-three suicide attempters diagnosed with schizophrenia and 87 sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
2
0
1
Order By: Relevance
“…Приводятся данные о том, что более четверти всех госпитализаций в психиатрический стационар с суицидальными попытками приходится на пациентов с шизофренией [23]. От 40% до 50% всех пациентов с шизофренией отмечают суицидальные мысли [24], а риск суицида, ассоциированный с данной рубрикой, в 12 раз выше, чем в общей популяции [25].…”
Section: Discussionunclassified
“…Приводятся данные о том, что более четверти всех госпитализаций в психиатрический стационар с суицидальными попытками приходится на пациентов с шизофренией [23]. От 40% до 50% всех пациентов с шизофренией отмечают суицидальные мысли [24], а риск суицида, ассоциированный с данной рубрикой, в 12 раз выше, чем в общей популяции [25].…”
Section: Discussionunclassified
“…A particular subject of interest was the association between suicide and mental health. Studies found that 77.5% of suicide attempters had mental health disorders, and 27.5% of suicide attempters had schizophrenia in particular, and 36.6% were depressed [ 28 ]. To sum it up, we can safely admit that research in the Arab is improving, quantitatively and especially qualitatively; over the years, articles targeting suicide are becoming more forthright, asking the right questions and addressing the issue directly.…”
Section: Discussionmentioning
confidence: 99%
“…Sixty percent of individuals with schizophrenia who die by suicide do so within the initial 4–10 years of being diagnosed. [ 5 6 ] A longer duration of untreated psychosis (DUP), multiple hospitalizations, immediate postdischarge period, a family history of psychiatric illness and suicide, a previous attempt, presence of positive symptoms, and depressive symptoms all are significant contributors to suicidal behavior in schizophrenia. [ 3 4 5 6 7 8 9 10 11 ]…”
Section: Introductionmentioning
confidence: 99%